2022
DOI: 10.1002/jcu.23134
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of efficacy of ultrasound‐guided microwave ablation in primary hyperparathyroidism

Abstract: Purpose: We aimed to evaluate the clinical efficacy and safety of ultrasonographically (US)-guided percutaneous microwave ablation (MWA) in the treatment of primary hyperparathyroidism (PHPT). Methods: A total of 35 patients who received MWA treatment in our hospital between August, 2019 and January, 2021 were retrospectively analyzed. Serum parathyroid hormone (PTH), calcium, phosphorus levels, and improvement in clinical symptoms were recorded before and after MWA. All patients were followed up for 6 months.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…Through high-frequency vibration, polar molecules (mostly water molecules) generate heat and rapidly rising temperature to 150 degrees Celsius results in cell dehydration necrosis (40). The MWA advantages include rapid temperature rise, high heat, short treatment period, extensive ablation range, and total inactivation of tumor tissue (41).…”
Section: Microwave Ablationmentioning
confidence: 99%
See 1 more Smart Citation
“…Through high-frequency vibration, polar molecules (mostly water molecules) generate heat and rapidly rising temperature to 150 degrees Celsius results in cell dehydration necrosis (40). The MWA advantages include rapid temperature rise, high heat, short treatment period, extensive ablation range, and total inactivation of tumor tissue (41).…”
Section: Microwave Ablationmentioning
confidence: 99%
“…Previously, Zhang et al perform MWA for PHPT treatment in 35 cases with six months follow-up. They concluded that MWA could significantly reduce serum PTH, calcium, and phosphorus levels; it was also relatively safe and long lasting in treating PHPT patients (41).…”
Section: Microwave Ablationmentioning
confidence: 99%
“…Longitudinal studies in PHP are mostly focused on post-operatory outcome between 1 and 3 years (up to 10 years) [13,75]. When assessing the early post-operatory QoL, the impact of PTx itself should be addressed [37,76,77]. A massive progress has been registered during the modern era of parathyroid surgery regardless of the initial clinical picture and associated complications/co-morbidities as seen in multiple endocrine neoplasia [53,77,78].…”
Section: Longitudinal Data On Php: Should Qol Assessment Find Its Way?mentioning
confidence: 99%